Chromosome-scale genome of the human blood fluke Schistosoma mekongi and its implications for public health - Minyu Zhou; Lian Xu; Dahua Xu; Wen Chen; Jehangir Khan; Yue Hu; Hui Huang; Hang Wei; Yiqing Zhang; Phiraphol Chusongsang; Kanthi Tanasarnprasert; Xiang Hu; et al. (BMC, 2023)
Abstract Background Schistosoma mekongi is a human blood fluke causing schistosomiasis that threatens approximately 1.5 million humans in the world. Nonetheless, the limited available S. mekongi genomic resources have hindered understanding of its biology and parasite-host interactions for disease management and pathogen control. The aim of our study was to integrate multiple technologies to construct a high-quality chromosome-level assembly of the S. mekongi genome. Methods The reference genome for S. mekongi was generated through integrating Illumina, PacBio sequencing, 10 × Genomics linked-read sequencing, and high-throughput chromosome conformation capture (Hi-C) methods. In this study, we conducted de novo assembly, alignment, and gene prediction to assemble and annotate the genome. Comparative genomics allowed us to compare genomes across different species, shedding light on conserved regions and evolutionary relationships. Additionally, our transcriptomic analysis focused on genes associated with parasite-snail interactions in S. mekongi infection. We employed gene ontology (GO) enrichment analysis for functional annotation of these genes. Results In the present study, the S. mekongi genome was both assembled into 8 pseudochromosomes with a length of 404 Mb, with contig N50 and scaffold N50 lengths of 1168 kb and 46,759 kb, respectively. We detected that 43% of the genome consists of repeat sequences and predicted 9103 protein-coding genes. We also focused on proteases, particularly leishmanolysin-like metalloproteases (M8), which are crucial in the invasion of hosts by 12 flatworm species. Through phylogenetic analysis, it was discovered that the M8 gene exhibits lineage-specific amplification among the genus Schistosoma. Lineage-specific expansion of M8 was observed in blood flukes. Additionally, the results of the RNA-seq revealed that a mass of genes related to metabolic and biosynthetic processes were up-regulated, which might be beneficial for cercaria production. Conclusions This study delivers a high-quality, chromosome-scale reference genome of S. mekongi, enhancing our understanding of the divergence and evolution of Schistosoma. The molecular research conducted here also plays a pivotal role in drug discovery and vaccine development. Furthermore, our work greatly advances the understanding of host-parasite interactions, providing crucial insights for schistosomiasis intervention strategies. Graphical Abstract